Effect of differents cultivars of Brazilian beans on intestinal health in vivo - Gomes, Mariana Juste Contin (2022)
Introduction: Beans are a legume widely consumed in Brazil and in the world, being especially rich in dietary fibers, proteins, and minerals. Carioca bean (Phaseolus vulgaris L.) has a promising chemical composition, with high content of proteins, rich in bioactive peptides, with functional potential in the health. BRSMG Madreperola is a cultivar of carioca bean used in this study due to its beneficial biological properties and low darkening along storage time. The intake of carioca bean and its protein hydrolyzate can modulate the intestinal microbiota and mitigating the effects of the high fat diet (HFD). In addition, beans are a promising crop for the biofortification of minerals such as zinc (Zn). Zn deficiency is one of the most prevalent nutritional deficiencies in Brazil and in the world, it impairs the quality of life of the population and generates an increase in the health expenditures. Cowpea (Vigna unguiculata L. Walp.) was target for Zn biofortification in Brazil. It has a large amount of dietary fibers, proteins, carbohydrates, starch, phenolic compounds, vitamins and minerals, including Zn. The high amount of dietary fibers (soluble and insoluble) present in cowpea beneficially affects intestinal health, favoring the growth of beneficial bacteria in the intestine, and improving the absorption of minerals. Furthermore, the use of Zn biofortified foods can be a good strategy to contribute to the reduction of Zn deficiency prevalence. However, the effects of the new cultivars of Zn biofortified cowpea in the intestinal functionality, gut microbiota, and mineral absorption, are not known. Objectives: (Review 1) To describe the effects of iron and Zn biofortified foods and gut microbiota in vivo. (Review 2) To analyze the effects of Zn biofortified foods on Zn status in humans. (Original Study 1) To evaluate the effect of the consumption of carioca bean flour and its protein hydrolyzate, associated with a HFD, on the modulation of the intestinal microbiota in vivo. (Original Study 2) To investigate the effects of soluble extracts of Zn biofortified cowpea on intestinal functionality and microbiota in vivo. Methods: Review articles were conducted according to PRISMA guidelines. Data search was performed at PubMed, Web of Science, Science Direct, and Scopus databases for experimental studies (Review 1), and PubMed, Cochrane, Scopus and Science Direct databases were searched for human studies (Review 2). For original study 1, 48 adult male BALB/c mice received a HFD associated or not with carioca bean flour or its protein hydrolyzate for nine weeks. Four experimental groups were designed (n=12): (1) AIN 93M diet + 0.5 mL of deionized water by gavage; (2) high fat diet + 0.5 mL 6-propyl-2- thiouracil (PTU) (10 mg/kg body weight) by gavage; (3) high fat diet added with carioca bean flour + 0.5 mL of PTU by gavage; (4) high fat diet + 0.5 mL of carioca bean protein hydrolyzate (700mg/Kg) + PTU by gavage. Intestinal function markers were assessed at the end of the study, and the gut microbiota was assessed by 16S rRNA gene sequencing. In the original study 2, the biological assay with intra-amniotic administration (Gallus gallus) was designed in seven experimental groups (n=10): (1) non-injected; (2) 18MΩH 2 O; (3) 50 mg/mL inulin; (4) 50 mg/mL BRS Pajeú bean (Zn standard); (5) 50 mg/mL BRS Aracê bean (Zn biofortified); (6) 50 mg/mL BRS Xiquexique bean (Zn biofortified) and (7) 50 mg/mL BRS Imponente bean (Zn biofortified). Evaluation of the intestinal morphology and intestinal functionality, as well as gut microbiota was performed at the end of the experiment. Results: Review 1 – Biofortified foods have positive effects on the composition and function of the gut microbiota, with an increase in Lactobacillus and Ruminococcus, producers of short chain fatty acids (SCFAs), and a decrease in pathogenic bacteria. Review 2 – Zn biofortified foods increase the Zn absorption in humans, favored by the lower phytate:Zn molar ratio in the studied food matrices. Advances in biofortification strategies to increase production, access, and consumption of Zn biofortified foods can contribute to improve the physiological state of Zn in vulnerable populations. Original study 1 – We observed an increase in Bacteroidetes and a reduction in the Firmicutes/Bacteroidetes ratio in the group that consumed a HFD associated with bean flour. In addition, this group showed an increase in cecum weight, moisture, and lipids content in the feces, compared to the controls. We did not observe changes in the gut microbiota of the group that consumed carioca bean protein hydrolyzate associated with the HFD, compared to the HFD control. Members of the Muribaculaceae family were more abundant in the group that consumed carioca bean flour, showing potential to improve the intestinal health. Functional analysis of the microbiota in this group showed a promising outcome of carioca beans in attenuating the effects of the HFD, without negatively altering its function. Original study 2 – There was a reduction in the abundance of Clostridium and E. coli in the groups treated with soluble extract of BRS Imponente and BRS Xiquexique beans (Zn biofortified). BRS Xiquexique increased the diameter and depth of the crypt, compared to the other groups. Gene expression of proteins involved with mineral absorption, brush border membrane (BBM) functionality and inflammation were similar to inulin and 18MΩH 2 O controls. However, the promising effects of BRS Xiquexique and BRS Imponente on improving the Zn transport by BBM, and BRS Xiquexique on intestinal morphology, indicate that these are promising cultivars to be considered by biofortification programs. Conclusion: Evidence suggests that the consumption of biofortified foods modifies the local microbial ecology, increasing the abundance of SCFA-producing bacteria and decreasing the abundance of potentially pathogenic bacteria. Carioca bean has dietary fibers which positively modulate the gut microbiota when associated with a HFD. Zn biofortified cowpea has the potential to improve the gut microbiota and increase the supply of Zn in the population. Keywords: Prebiotic. Bioactive peptides. Mineral metabolism. Gallus gallus. Intra-amniotic administration. Microbiome.